Design and Development of Five Parallel Engines for Lubricantsand Fuel Testing Experimental Rigs, Part 3 - M., Hazim; L., Chee Wai; G., Devandran; M., Khalid; M., Hanis (2015)
An engine test rig could serve for further analysis for researcher to study about engine which it isdepends on the type of applications needed. It is all depends on the properties and concept focused to be study for researcher about the engines and how the surrounding factors could affect the rate. Therefore a mechanical design of five parallel engine arrangement for lubricant and fuel testing experimental test rig have been develop. The purpose of this experiment is to study the rate of weariness effectson engines components such as crankshaft, pistons, and piston valves. Same type of five grass cutterengines were used and it is arranged parallel in thetest rig. In this test, the engines were run for few hours with the applied ofa solid cylinder rodwhich fixed to shaft connecting part of engine as a load for this experiment. The rate of weariness of each components of engines are further analysed based on the hours of engine run and the throttle turns that have been set up in Arduino software through computer